ANALISIS PERAMALAN PERENCANAAN BIAYA PENGELOLAAN PETERNAKAN KAMBING PE DENGAN METODE EXPONENTIAL SMOOTHING - Yulis Wulandari, Dian; Purnama Lubis, Hidayati; Franita, Riska; Amanda, Adelia (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2023)
Exponential Smoothing is a procedure for continuous improvement in the forecasting of the latest observed objects. In this study, Exponential Smoothing is used to predict the income level of Etawa Peranakan (PE) Goats in the Al-Amin Science and Industrial Park Area which plans to create an area with a Life Cycling System. Where every field or sector in the area is connected, environmentally friendly, minimizes waste in each sector, and can even become a place for learning and traveling (Edutourism). The income of the Etawa Peranakan Goat business comes from the sale of male PE goats with an age of more than 1 year, the sale of fresh pure milk, and the sale of goat manure. Sales of Goat Urine. By using the Exponential Smoothing Method in the 5th year, the amount of income received after expenses for feed and vitamins was Rp. 2,564,443,875 with a total of 4 adult male PE goats and 874 female PE goats. With an alpha value of 0.87 and an error rate in this calculation of 30%.